Simulasi Tcp-Ip Menggunakan Topologi Bus Pada Aplikasi Cisco Paket Tracer - Lutfi Apriyadi; Desta Adji Saputra; Muhammad Azka Alwafi; Didik Aribowo; Sonata Mahardika (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In an increasingly modern era, developments in information and communication technology continue to take place in parallel. There are various telecommunications systems that have been developed, allowing humans to communicate effectively, both directly and over long distances. With the evolution of telecommunications systems, the variety of systems used continues to grow, offering various ways for us to interact. This research aims to explore the efficiency of a topology that has been proven previously, by creating relevant simulations using the Cisco Packet Tracer application. Through this simulation, it can be proven that the bus topology still has high competitiveness in telecommunications infrastructure, especially in the connection process between servers and other devices. Researching and understanding the performance of topologies like this is important for optimizing our modern communications systems.